Understanding teachers ' technological and pedagogical knowledge at the University of Dar es Salaam in the New Normal Era: Situating teaching in the TPACK Framework - Raphael, Christina; Mtebe, Joel S. (University of Dar es Salaam Library Journal, 2024)
This study investigates the integration and application of Technological Pedagogical Content Knowledge (TPACK) within the University of Dar es Salaam during the transformative phase of the COVID-19 pandemic, termed as the 'New Normal'. The research seeks to explore how instructors have adapted to the abrupt transition to digital learning platforms, with a focus on the interplay between technology, pedagogy, and content. Utilizing both qualitative and quantitative analyses with 111 instructors across 16 colleges, the study assesses the proficiency and challenges faced by instructors in integrating TPACK in their teaching methods. The findings demonstrate a significant impact of TPACK on enhancing teaching effectiveness and student engagement in a digitally-driven academic setting. Furthermore, the study highlights critical barriers to the adoption of TPACK, including infrastructural constraints and the necessity for continuous professional development. The paper concludes by providing insights into the prospects of TPACK in higher education, underscoring its role in fostering resilient and adaptable educational frameworks to confront global challenges such as the COVID-19 pandemic.